“Mapping the Correlation Between Fingerprint Pore Diameter and Chronological Age” (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Fingerprints are unique dermatoglyphic patterns found on the volar surfaces of the fingertips, characterized by ridges and furrows. Poroscopy, the systematic examination of sweat pores located along these ridges, is a significant technique in forensic identification due to the individual specificity of pore configurations. While previous research has established the uniqueness and consistency of pore patterns, the potential influence of aging on these characteristics remains insufficiently studied. Current literature offers limited insight into agerelated changes in pore size, morphology, or visibility, and there is a notable absence of longitudinal data and diverse age cohort studies to fully address this issue. This study aims to address this gap by systematically analysing pore features across four distinct age cohorts: adolescents and young adults (13–24 years), middleaged adults (25–48 years), older adults (49–60 years), and senior adults (60+ years). A total of 400 fingerprint samples were collected from these groups. Fingerprint impressions were obtained using an inkless ink pad on glossy paper, selected for its ability to produce high-resolution prints with clearly visible pores. Adequate pressure was applied to ensure optimal ridge and pore detail. The collection sequence commenced with the right thumb and concluded with the left little finger, with ten prints gathered per age cohort. A mirrorless camera equipped with a fixed focal length and zoom lens was employed for print documentation. The number of pores per ridge segment was manually quantified to calculate the average pore diameter. The results demonstrate the considerable potential of poroscopy in forensic age estimation, highlighting its utility as a supplementary tool for approximating the age of an individual from latent fingerprint evidence recovered at crime scenes.